Strengthening The Skill Of Creativity And Innovation In Pre-Primary And Primary School Education (International Journal of Applied Research in Management and Economics, 2018)
In the present age, students must improve their critical and creative thinking skills in order to make the right decision and solve complex social problems to deal with the tremendous transformations of the third millennium. They should increase the research and problem-solving skills and the searching spirit. Obviously, in order to achieve these goals, there is a heavy responsibility for education centers, especially education. These centers, on the one hand, undertake the task of teaching knowledge and equipping students with the information needed, and on the other hand, they have to provide a context to help the development and growth of creativity and innovation and the correct use of this talent and ability. Creativity is the use of mental abilities to create a new thought or concept, the process of creating new thoughts and converting those thoughts into action and useful applications is called innovation. After expressing the importance and necessity of developing children’s creativity, this paper investigates the history of the subject, the concept of creativity and imagination from birth to six-year-olds, the effect of game in developing creativity for pre-primary and primary school education, the characteristics of creativity in children, creative teaching methods, important principles in developing creativity in pre-primary and primary school education and … In the end, by the mention of the factors preventing creativity and initiative in the students, suggestions and practical solutions for the use of parents, instructors and agents have been raised. Hope to be a grower of creative, innovative, faithful, and very dynamic and capable children.